Analisis Pemberian Pinjaman Kredit Pada Usaha Ekonomi Desa Simpan Pinjam (UED-SP) Maju Bersama Desa Suka Maju Kabupaten Rokan Hulu. - FATIMAH, SITI (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
The purpose of this study was to determine the lending analysis applied by the Usaha Ekonomi Desa Simpan pinjam (UED-SP) Maju bersama. The sample in this study amounted to 44 respondents ie borrowers Fund UED-SP Maju bersama. The data used are secondary data yiatu report delinquent customers UED-SP maju bersama. Data analysis technique used in this study is a qualitative descriptive analysis. From the results of the analysis showed that occurred arrears on UED-SP Maju bersama Rp 500,000, - to Rp 3,000,000, -. The percentage of non-payment by the customer is the highest in the plantation business customers is 81.9%, this is due to the price of farm products is very low so that customers experiencing financial problems and are unable to pay loan installments. It can be concluded that the arrears still occur despite lending system has been implemented well. However, bad credit problems can be minimized by applying the principle of 5 C.